Psychoeducation: Identification of Characteristics, Behavioral Characteristics, and Special Potentials of Students with Special Needs at SLB ‘Aisyiyah Porong: Psikoedukasi: Identifikasi Karakteristik, Ciri Perilaku, dan Potensi Istimewa Siswa Berkebutuhan Khusus di SLB ‘Aisyiyah Porong - Laili, Nurfi; Fahmawati , Zaki Nur; Wachidah, Kemil (Procedia of Social Sciences and Humanities, 2022)
Special schools (SLB) are a form of formal education that is devoted to managing students with special needs in terms of their development and academics. The various types of special needs of these students require a comprehensive theoretical understanding of the behavioral characteristics of each type. This makes teachers who teach in special schools are required to have the ability and sensitivity in identifying students based on their distinctive behavioral characteristics. This service activity aims to provide knowledge to teachers about the characteristics of students with special needs and the importance of the identification process in the teaching and learning process. The method used is psychoeducational activities regarding the characteristics of students with special needs. The results of this activity indicate that there is an increase in the understanding of teachers regarding the characteristics, behavioral characteristics and special potential of each type of disability of students with special needs